Retrospective Analysis of Higher University Education in Russia and Abroad - V V Zakharyascheva (Peoples' Friendship University of Russia (RUDN University), 2012)
The article analyzes the features of the development of higher university education in Russia and abroad. A special attention is given to the Russian higher education.